A load profile study of different buildings to identify neighborhood energy flexibility with exchange possibilities. (September 2017) - Walker, Shalika; Corten, Kai; Labeodan, Timilehin; Maassen, Wim; Zeiler, Wim
Abstract: Buildings are a key source of energy flexibility due to their high energy demand. Harnessing the energy flexibility of buildings, however, demands that buildings be considered collectively. This paper presents preliminary results to discover building's energy flexibility, from two different neighborhoods in the Netherlands. The energy demand profiles of three large buildings in each neighborhood are analyzed to identify possible useful simultaneous heating and cooling loads. Finally, the possibility for energy exchange between these buildings is explored.